Lipschitz conditions for random processes from Banach spaces Fψ(Ω) of random variables - Zatula, D.V.; Kozachenko, Yu.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
We study the Lipschitz continuity of random processes from Banach spaces Fψ(Ω) and obtain the estimates for a distribution of the norms of such processes.